Pendampingan Inovasi dan Pemasaran Melalui Digital Marketing UMKM Tape Ketan Hitam di Desa Nguling Pasuruan - Wiwin Fachrudin Yusuf; M. Sulhan; Nur Aziziyah; Nadyatus Syarifah; Muhammad Johar Ulinnuha; Abas Abas; Ardilla Khusliana Sari; Kristie Andriyani; Mayang Mayang; Muhammad Rifqi Eryan (GUYUB: Journal of Community Engagement, 2024)
Community service for black sticky rice tape MSMEs in Nguling Village, Nguling District, Pasuruan Regency aims to provide assistance in innovating products and marketing digitally. The implementation method for this activity uses the ABCD (Asset based community development) method, the steps in implementation include five steps, namely discovery (discover), dream (dream), design (plan), define (determine), destiny (do). The result of community service in this activity is that MSME actors can understand the importance of product innovation and digital marketing and change traditional behavior to modern ones. MSME actors can also apply the results of assistance to their products. As for the implementation of this service, MSME actors receive direct training and assistance regarding product innovation and digital marketing from resource persons or practitioners who are professionals in their fields. Ultimately, all parties hope that this impact will take place in a sustainable manner to achieve the mutually expected goals.